Answer to Question 31C-1

For reference, here is the equation that we must show is false.

  isPrefix(h : t, L) = isPrefix(t, L)

There are many counterexamples. How about h = 1, t = [2], L = [2,2]. The left-hand side of the equation is

   isPrefix(1 : [2], [2,2])
   = isPrefix([1,2], [2,2])
   = false  since [1,2] is not a prefix of [2,2].

The right-hand side of the equation is

   isPrefix([2], [2,2])
   = true  since [2] is a prefix of [2,2].

The two sides are not the same for this example.